Determinants Of Capital Market Investment Interest In The Millenial Generation In The Covid-19 Pandemic - Biggita Berliana; Sri Dwi Ari Ambarwati; Aryono Yacobus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The increase in investment interest during the COVID-19 pandemic is influenced by various factors. This study aims to show the factors that can influence investment interest in the capital market in the millennial generation during the covid-19 pandemic. The data analysis technique used is multiple linear regression with SPSS application. The results showed: motivation, technological progress, investment returns, investment risk, and social media had a significant positive effect and financial literacy and minimum investment capital had a significant negative effect on investment interest. Application/Originality/Value: This study examines more independent variables than previous studies and this study finds that financial literacy actually has the opposite effect on investment interest during the COVID-19 pandemic. This is in line with the existing phenomenon that the high interest in investing in the millennial generation during the COVID-19 pandemic is not matched by a high level of financial literacy. Keywords: Motivation, Technological Advancement, Financial Literacy, Minimum Investment Capital, Investment Return, Investment Risk, Social Media, Investment Interest, Millennial Generation.